2020
DOI: 10.1002/mp.14104
|View full text |Cite
|
Sign up to set email alerts
|

Homology‐based radiomic features for prediction of the prognosis of lung cancer based on CT‐based radiomics

Abstract: Purpose: Radiomics is a new technique that enables noninvasive prognostic prediction by extracting features from medical images. Homology is a concept used in many branches of algebra and topology that can quantify the contact degree. In the present study, we developed homology-based radiomic features to predict the prognosis of non-small-cell lung cancer (NSCLC) patients and then evaluated the accuracy of this prediction method. Methods: Four datasets were used: two to provide training and test data and two f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 21 publications
(47 reference statements)
1
26
0
Order By: Relevance
“…Other groups have worked on smaller datasets and reported comparable results on subsets of the data when using smaller numbers of segmentation outlines [ 18 , 26 , 27 ]. For the NSCLC dataset, Kadoya et al found a C-index of 0.625 for a multivariate radiomic feature model [ 28 ]. In contrast, Fu et al reported a C-Index of 0.67 when applying neural networks on the BRATS dataset [ 29 ], thereby indicating that deep learning-based approaches may achieve higher C-indices.…”
Section: Discussionmentioning
confidence: 99%
“…Other groups have worked on smaller datasets and reported comparable results on subsets of the data when using smaller numbers of segmentation outlines [ 18 , 26 , 27 ]. For the NSCLC dataset, Kadoya et al found a C-index of 0.625 for a multivariate radiomic feature model [ 28 ]. In contrast, Fu et al reported a C-Index of 0.67 when applying neural networks on the BRATS dataset [ 29 ], thereby indicating that deep learning-based approaches may achieve higher C-indices.…”
Section: Discussionmentioning
confidence: 99%
“…Feature Selection 1 (FS1) selects only robust features using test-retest and multiple segmentation [9,24]. The test-retest method uses a dataset created by Zhao et al to evaluate the variability of tumor unidimensional, bidimensional, and volumetric measurements on same-day repeat CT scans [25].…”
Section: Feature Selectionmentioning
confidence: 99%
“…The test-retest method applies a radiomic analysis of tumors to two images of each patient and excludes features that significantly change over this short time as being less robust. The concordance correlation coefficient (CCC) served to evaluate the agreement between the values of two features, and feature selection was performed with CCC > 0.85 [24,27,28]. The multiple segmentation method uses a dataset created by van Baardwijk et al to investigate whether auto-delineation reduces the interobserver variability compared to manual PET-CT-based GTV delineation [29].…”
Section: Feature Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Betti numbers (BNs), which are topological invariant in the homology, has been applied to quantify tumor traits in several medical images such as CT, magnetic resonance, and pathological images [13][14][15][16][17]. The topologically invariants in the BNs indicates unchangeable property of objects under continuous deformation [18].…”
Section: Introductionmentioning
confidence: 99%